Representasi Alam dan Perempuan dalam Film Perempuan Tanah Jahanam Karya Joko Anwar: Tinjauan Ekofeminisme: Representation of Nature and Women in Joko Anwar's Film Perempuan Tanah Jahanam: An Ecofeminist Perspective - Dhea Larasati; Yusra D; Deri Rachmad Pratama (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to examine the representation of nature and women in the film Perempuan Tanah Jahanam directed by Joko Anwar through an ecofeminist perspective. Employing a qualitative descriptive approach, the analysis focuses on dialogues and events that represent the relationship between nature, women, and patriarchal social structures. The findings indicate that nature is represented as an entity possessing subjectivity and intrinsic value, functioning as a space of memory and recovery from collective violence. Women are portrayed as experiencing exploitation and violence within patriarchal systems, yet they also demonstrate active forms of resistance through symbolic and transformative actions. The relationship between nature and women reveals a structural interconnectedness, in which both are positioned as victims of patriarchal and capitalist logics of domination. These findings underscore that Perempuan Tanah Jahanam articulates a critique of power relations that simultaneously oppress women and degrade nature.